FACEMASK: A SUBTLE TOPIC OF MICROPLASTIC INDUCED HEALTH AND ENVIRONMENTAL CONCERN IN BANGLADESH DURING COVID-19 (American International Journal of Nursing Education and Practice, 2021)
This editorial focuses on the imperceptible side effects of widespread use of facemask especially during COVID-19 pandemic in context of Bangladesh. Both single used facemask and reusable fabricated facemasks are creating extra load on regular waste streams and accelerating the chance of microplastic leaching in various ways. In Bangladesh, a significant amount of fabricated and non-fabricated facemasks is using everyday alike the other countries of the world. This aggravated usage of facemasks tends to create microplsatic pollution that pose potential threat to both environment and human health. However, no significant studies have been done yet that focused on the imperceptible side effects of facemasks wearing by huge population of the country like Bangladesh. It is high time to bring this subtle effects to lime light and seek attention of the researchers to make scientific solution in a sustainable way.JEL Classification Codes: Q53, I12.